Implementation of Wideband Acoustic Immittance in Clinical Practice: Relationships among Audiologic and Otologic Findings - Sanford, Chris A.; Brockett, Jeff E.; Aithal, Venkatesh; AlMakadma, Hammam (Seminars in Hearing, 2023)
A number of studies have produced normative and developmental data and examples of wideband acoustic immittance (WAI) obtained in ears with pathologies and or dysfunction. However, incorporation of this tool into clinical audiology and otolaryngology practice has been slower than expected, potentially due to challenges with interpretation, integration into existing test batteries, and confidence in practical application. This article presents information aimed at helping clinicians increase their confidence in using this new tool by becoming more familiar and making connections with the ways that WAI outcomes both align with and add to standard immittance, audiometric and otologic diagnostic test outcomes. This article presents several case studies to demonstrate the use of WAI in realistic clinical settings. Each case presents a brief background, case history, audiologic/otologic findings, and initial recommendations, followed by a discussion on how the inclusion of WAI test outcomes aids in diagnostic decisions. The overall aim of this work is to identify the relationships among different diagnostic test outcomes, to demonstrate basic WAI interpretation principles, and encourage the reader to engage with this diagnostic tool in clinical practice.
Keywords: wideband acoustic immittance; absorbance; tympanometry; middle ear disorders; audiology; otolaryngology